Comparative in vitro toxicity of compositionally distinct thermal spray particulates in human bronchial cells - E.S. Burns; R.E. Harner; V. Kodali; A.A. Afshari; J.M. Antonini; S.S. Leonard (Toxicology Reports)
Thermal spray, in general, is a process that involves forcing a melted substance, such as metal or ceramic in the form of wire or powder, onto the surface of a targeted object to enhance its desired surface properties. In this paper, the melted substance is metal wire generated by an electric arc and forcibly coated on a rotary iron substrate using compressed air. This thermal process is referred to as double-wire arc thermal spray. The particles generated through these methods fall within the nanometer to micrometer agglomerate size range. There is concern regarding potential human health outcomes as these particles exhibit a similarity in particle morphology to welding fumes. Thermal spray wires with zinc (PMET540), iron and chromium (PMET731), and nickel (PMET885) as primary metal compositions were used to generate particulate via an electric arc wire thermal spray generator for exposure to human bronchial cells (BEAS-2B) to examine comparative toxicity ranging from 0 to 200 µg/mL. Resulting cellular viability was assessed through live cell counts, and percent cytotoxicity was measured as a function of LDH release. Oxidative stress, genotoxicity, and alteration in total antioxidant capacity were evaluated through DNA damage (COMET analysis) and antioxidant concentration at 0, 3.125, 25, and 100 µg/mL. Protein markers for endothelin-1 (ET-1), interleukin-6 (IL-6), and interleukin-8 (IL-8) were also assessed to determine inflammation and endothelial alteration. Results: indicate modulation of oxidative stress response in a material and dose dependent manner. PMET540 exhibited the greatest cytotoxic effect between wires and across doses. DNA damage and antioxidant concentration induced by PMET540 were significantly higher than other wires at higher doses (DNA damage increased at 25 and 100 µg/mL; Antioxidant concentration increased at 100 µg/mL). However, ET-1 concentration significantly increased only after application of 100 µg/mL PMET885. IL-6 and IL-8 were most highly expressed in BEAS2B culture after 25 µg/mL exposure to PMET540 (99.4 % Zn). This data suggests that metal composition of thermal spray wires dictates the diverse response in human bronchial cells.